YOGYAKARTA KOTA PENDIDIKAN: PERUBAHAN SOSIAL KOTA YOGYAKARTA 1880-1930 - Filipus Dimas Darumurti (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2023)
Yogyakarta is a city that continues to change, grow and develop with its social dynamics. This social change in the city of Yogyakarta has a significant impact on the development of education in Yogyakarta. This study aims to explain the social changes of the people of the city of Yogyakarta and explain the dynamics of the development of education in Yogyakarta in 1880-1930. The method used in this research is to use a literature study with analytical descriptive. This research shows that the situation of the palace and the colonial situation influenced the social changes of the city of Yogyakarta in various fields of life, including the field of education. The dynamics of the development of education in Yogyakarta is growing rapidly with the presence of various schools of various types which are managed by the government and the private sector. Finally, Yogyakarta has the characteristics of education so that it is known as the city of education.Keywords: Social Change, Education, Yogyakarta City